The Origin of Continents and Oceans : A. Wegener (translated by J. Biram from the 4th revised German edition, 1929) Dover, New York N.Y., 1966, 246 pp., 63 illus., paperbound U.S.$2.00 - Bemmelen, R.W. van (Elsevier, 1968)
In the old controversy between fixism and mobilism a new scientific tool, palaeomagnetism, has recently brought forward independent diagnostic facts. In the discussions about drift many authors quote Wegener's classic work. It is fortunate that it has now appeared in an excellent English translation by John Biram.
Keywords: Aardwetenschappen